A case of hepatic paragonimiasis was misdiagnosed as hepatocellular carcinoma with rupture and haemorrhage. Issue 6 (June 2021) - Jin, Wen-Xiang; Li, Tie-Han; Zhu, Hong; Zhu, Lei
Paragonimiasis is a disease caused by parasitic infections that mainly involve the lungs. However, it can also produce ectopic infections, such as when the parasites invade the liver, brain and subcutaneous tissue, which then cause different symptoms. This current case report describes a 55-year-old male patient with hepatic paragonimiasis that was misdiagnosed as liver cancer with rupture and haemorrhage. The initial computed tomography findings suggested ruptured liver cancer. The patient underwent laparoscopic right hemihepatectomy. Postoperative pathological analysis resulted in a diagnosis of hepatic paragonimiasis. The patient recovered well postoperatively and was treated with 25 mg/kg praziquantel orally three times a day for 3 days after discharge with good efficacy. In this present case, the rupture and haemorrhage of the liver mass made it difficult for the treating physicians to consider hepatic paragonimiasis, which lead to the initial misdiagnosis of this patient. Although paragonimiasis is very rare, medical staff should be vigilant and have a comprehensive understanding of the different diseases that can cause liver masses so that misdiagnosis can be avoided.